Polyvinyl alcohol coating prevents platelet adsorption and improves mechanical property of polycaprolactone-based small-caliber vascular graft - Wakabayashi, Naohiro; Yoshida, Takumi; Oyama, Kyohei; Naruse, Daisuke; Tsutsui, Masahiro; Kikuchi, Yuta; Koga, Daisuke; Kamiya, Hiroyuki (Frontiers in Cardiovascular Medicine, 2022)
The low patency of synthetic vascular grafts hinders their practical applicability. Polyvinyl alcohol (PVA) is a non-toxic, highly hydrophilic polymer; thus, we created a PVA-coated polycaprolactone (PCL) nanofiber vascular graft (PVA–PCL graft). In this study, we examine whether PVA could improve the hydrophilicity of PCL grafts and evaluate its in vivo performance using a rat aorta implantation model. A PCL graft with an inner diameter of 1 mm is created using electrospinning (control). The PCL nanofibers are coated with PVA, resulting in a PVA–PCL graft. Mechanical property tests demonstrate that the PVA coating significantly increases the stiffness and resilience of the PCL graft. The PVA–PCL surface exhibits a much smaller sessile drop contact angle when compared with that of the control, indicating that the PVA coating has hydrophilic properties. Additionally, the PVA–PCL graft shows significantly less platelet adsorption than the control. The proposed PVA–PCL graft is implanted into the rat’s abdominal aorta, and its in vivo performance is tested at 8 weeks. The patency rate is 83.3% (10/12). Histological analysis demonstrates autologous cell engraftment on and inside the scaffold, as well as CD31/α−smooth muscle positive neointima regeneration on the graft lumen. Thus, the PVA–PCL grafts exhibit biocompatibility in the rat model, which suggests that the PVA coating is a promising approach for functionalizing PCL.